(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
Due to the fact that the conceptualization of reality and the ability of making judgments are greatly influenced by the speaker’s emotions and current mood, the main aim of this research is to emphasize the effect of emotions on modal statement. The methodology entails literature review which offers an insight into the aspects of modality followed by the corpus analysis of a dialogue between the two protagonists from Daisy Miller by Henry James. It is concluded that the modal strength of modal verbs depends on the intensity of emotion.